소뇌위축으로 인한 실조 증례 보고 - 이재섭; 황하연; 주정현; 장우석; 백경민; Lee, Jae-Seob; Hwang, Ha-Yeon; Joo, Jeong-Hyun; Jang, Woo-Seok; Baek, Kyung-Min (대한한방내과학회지, 2014)
Objectives: This study is a report of the clinical application of traditional Korean medicine on ataxia with cerebellar atrophy. Methods: The ataxia in this case occurred 5 years ago. The symptoms had been getting worse until the patient came to hospital. The MRI of this patient showed atrophy of the cerebellum. We measured the state of this case with the Korean version of the Berg Balance Scale (K-BBS), before and after treatment and Numeric Rating Scale-11 (NRS-11) of the symptoms, every week. We treated the case with traditional Korean medicine such as acupuncture and Gamiyukmijihwang-tang. Results: After treatment, the score of K-BBS increased, while the score of NRS-11 decreased. Conclusions: According to this study, traditional Korean medicine is effective for controlling ataxia caused by cerebellar atrophy.